2014
DOI: 10.1155/2014/934848
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Metabolomics forIn SituMonitoring of Wound Healing

Abstract: Wound healing of soft tissue and bone defects is a complex process in which cellular differentiation and adaption are regulated by internal and external factors, among them are many different proteins. In contrast to insights into the significance of various single proteins based on model systems, the knowledge about the processes at the actual site of wound healing is still limited. This is caused by a general lack of methods that allow sampling of extracellular factors, metabolites, and proteins in situ. Sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…As discussed in the introduction, targeted and untargeted metabolomics approaches have only recently been applied to wound healing studies, but never in conjugation with a wound healing treatment [33, 34]. For this study, focus was placed on dysregulated metabolites that were classified based on their functional pathways, then these individual metabolites were targeted based on their connected wound healing processes and direct impact on the tissue of interest (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in the introduction, targeted and untargeted metabolomics approaches have only recently been applied to wound healing studies, but never in conjugation with a wound healing treatment [33, 34]. For this study, focus was placed on dysregulated metabolites that were classified based on their functional pathways, then these individual metabolites were targeted based on their connected wound healing processes and direct impact on the tissue of interest (Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the need has been highlighted for high throughput biological techniques such as metabolomics, proteomics, and genomics to reveal new understanding of wound healing [32]. In a recent study, wound fluid samples were analyzed with proteomics and metabolomics to improve the understanding of bone defects and its connection to the biochemical mechanisms in the wound environment [33]. Another study used metabolomics profiling of diabetic and non-diabetic wounds in mice and identified key metabolites that were differentially regulated and could serve as future biomarkers [34].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome of wound healing has been understudied. Only two animal studies [9,10] and three human studies [11][12][13] have investigated the metabolic profile of cutaneous wounds at a single time-point using a metabolomics approach. In addition other "omic" technologies such as genomics have been utilised to assess the progressive changes in gene expression in wound healing over time [14,15].…”
mentioning
confidence: 99%
“…For example, although Raldh and NOS are upregulated in multiple species, different injury‐induced inputs may underlie this activation. Recent progress in high‐throughput proteomic and metabolomic approaches (Boser et al, ; Kalkhof et al, ; Looso et al, ; Natarajan, Ramakrishnan, Lakshmanan, Palakodeti, & Rangiah, ; J. Zhao et al, ) will enable the study of transcription‐independent processes launched upon injury. New regulators of IIHP are likely to be discovered with the advent of new technology, for example, development of fluorometric sensors for a wide array of small molecules as dNTPs and of high sensitivity H 2 O 2 sensors that enable more effective detection of diffusible molecules at very low concentrations (Mugoni, Camporeale, & Santoro, ; Sprenger & Nikolaev, ; Zheng, Peng, Jiang, Wang, & Xu, ).…”
Section: Discussionmentioning
confidence: 99%